PENGARUH CELEBRITY ENDORSER TERHADAP MINAT PEMBELIAN PRODUK AIDI.ID (STUDI PADA FOLLOWERS INSTAGRAM AIDI.ID) - Dinda Septiani Audia; Roni Jayawinangun; Feri Ferdinan (Jurnal Penelitian Sosial Ilmu Komunikasi, 2019)
ABSTRACTThis research focuses on the use of celebrity endorser to increase the interest of buying a product with title "The Impact of Celebrity Endorser towards Interest of Purchasing Aidi.id Products (study on Aidi.id Instagram Followers)â€. The data analysis technique in this research is descriptive analysis, and using transformation of ordinal data into interval with MSI (Method of Successive Interval), equal score, and classic assumption as well as double regretion.The result of this research shows that the customer interest of purchasing Aidi.id product is categorized as high, this is based on the value of transactional purchase interest, referential purchase interest, preferential purchase interest, and explorative purchase interest which are respectively on very high category. There is a significant factor of the celebrity endorser that increases the customer interest in purchasing Aidi.id products. Attractiveness factor, trustworthiness factor, and expertise factor simultaneously bring impact to the buying interest that can be seen from F Test result with the amount of .000 with the percentage of 51.3% that explains the interest variation, and the other 48.7% influenced by other variables. Keywords: Celebrity Endorser, Purchase Intention, Instagram, Aidi.id